Iron deficiency – a factor in left ventricular ejection fraction depression post-myocardial infarction. (14th October 2021) - Dias Claudio, F; Carias, M; Rocha, R; Picarra, B; Neves, D; Trinca, M
Abstract: Introduction: Iron deficiency was shown to affect functional capacity and ejection fraction in patients with heart failure and reduced ejection fraction. Myocardial infarction is an important cause of reduced left ventricular ejection fraction (LVEF). Moreover, there is some evidence of the iron deficiency as a factor to predict cardiovascular and non-cardiovascular mortality. Purpose: Evaluate the presence of iron deficiency in patients with acute coronary syndromes (ACS) admitted to the intensive cardiac care unit and its eventual association with LVEF and mortality. Population and methods: We performed a prospective study in which ACS patients were divided into groups according to the presence or absence of iron deficiency. We collected demographic data, comorbidities, as well as determination of troponin I, haemoglobin and criteria for absolute and functional iron deficiency (ID) and other data related to the use of mechanical ventilation, need for aminergic support, LVEF and death. Results: From 148 patients we included 78 patients who met the criteria for being analysed. 49 patients had iron deficiency (51% had absolute iron deficiency and 49% had relative iron deficiency). There were no differences between groups in terms of myocardial infarction with or without ST segment elevation (p=0.609 and p=0.329, respectively), hypertension (p=0.926), diabetes (p=0.882), obesity (p=0.343), dyslipidaemia (p=0.482), smoking (p=0.876), valvular heart disease (p=0.888), acute and chronic renal failure (p=0.800 and p=0.888, respectively) and LVEF (p=0.886). There were no differences in need for aminergic support (p=0.984), ventilation (p=0.315) and death (p=0.704). We found that in the sub-population of patients without anaemia (Hb>12g/dL), the proportion of patients with depressed LVEF (inferior to 50%) and relative iron deficiency was significantly higher than those with preserved LVEF (48.1 vs 13.8%, p=0.005). Furthermore, we also found that in this sub-population, patients with myocardial infarction without ST segment elevation had higher proportion of absolute iron deficiency (45.0 vs 19.4%, p=0.043). Conclusion: Our study showed that the prevalence of iron deficiency in ACS patients is 62.9% (n=49). Moreover, in patients without anaemia, this results seems to point out that the presence of iron deficiency may be related with LVEF, at least during the acute event. Further studies with a higher sample size are warranted to either establish or discard this association. Furthermore, a follow-up of this patients can further enlighten us as to the role of iron deficiency in long term LVEF and mortality. FUNDunding Acknowledgement: Type of funding sources: None.